Pemanfaatan Podcast Sebagai Sarana Transformasi Mindset Mahasiswa: Studi Podcast “Bahas Aja Eps Gen Z, Malas & Pengangguran” - Ita Hidayati; Hafna Nadhifa Syarifa; Muhammad Kevin Kadhafi; Moch. Aldi Azizul Hakim; Kamunoyoso Agung Nugroho; Rifqi Rohmanul Khakim (Advances In Education Journal, 2026)
Negative Stereotypes Regarding Gen Z's Work Ethic, Such As Laziness And Lack Of Discipline, Continue To Develop In Society And Potentially Influence The Identity Formation Of Young Generations. This Study Aims To Examine The Effectiveness Of Podcasts As A Medium For Transforming Students' Mindset, Taking A Case Study Of The Episode "Bahas Aja: Gen Z, Generasi Malas & Pengangguran?". The Method Used Is A Descriptive Quantitative Survey Through An Online Questionnaire (Google Forms) Distributed To Gen Z Students. Data Were Analyzed Using Percentages To See The Distribution Of Responses Across Four Main Indicators: Work Ethic Stereotypes, Study Habits And Discipline, Changes In Perspective After Listening To The Podcast, And The Relevance Of The Consistency Message. The Results Showed That 65% Of Respondents Acknowledged That Negative Stereotypes About Gen Z's Work Ethic Have A Basis In Social Reality, While 49% Rated Their Study Habits And Self-Discipline As Quite Good. More Significantly, All Respondents Reported A Change In Perspective After Listening To The Podcast (64% Changed, 36% Changed Moderately). All Respondents Also Rated The Message That Consistency Is More Important Than Talent As Relevant To Themselves. Furthermore, Respondents Rejected The Generalization Of The Label "Lazy" To All Gen Z Because They Consider Individual Context To Be Very Influential. Overall, The Podcast Proved Effective As A Means Of Transforming Students' Mindset, Particularly In Correcting Perceptions Of Generational Stereotypes And Instilling The Value Of Consistency. This Study Recommends The Use Of Podcasts As An Educational Intervention Medium In Higher Education Settings.